2018
DOI: 10.5694/mja17.00400
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of medical student selection tools in Australia and New Zealand

Abstract: The known The predictive power of composite scores based on the weighted means of the results from multiple selection tools is low, explaining less than 15% of variance in student outcomes, regardless of the statistical models, selection tools, and outcomes used.The new Discriminant function analysis yields optimal and meaningful cut-scores for each of the selection tools based on binary outcomes. A non-compensatory selection model or a "sufficient evidence" approach to selection would be useful for some medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 21 publications
0
33
0
2
Order By: Relevance
“…For example at the University of New South Wales, Sydney, Australia (UNSW) only about one in ten applicants succeed in securing a place in the Medicine program. Medical schools apply a range of selection methods to ensure that admitted students succeed in the program, complete the their studies in a timely manner and become competent junior doctors [2]. The most common selection tools used by Australian undergraduate medical schools is the Australian Tertiary Admission Rank (ATAR) or equivalent, which is a score between 0.00 and 99.95 based on high school matriculation examinations, indicating a student's position in their cohort [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example at the University of New South Wales, Sydney, Australia (UNSW) only about one in ten applicants succeed in securing a place in the Medicine program. Medical schools apply a range of selection methods to ensure that admitted students succeed in the program, complete the their studies in a timely manner and become competent junior doctors [2]. The most common selection tools used by Australian undergraduate medical schools is the Australian Tertiary Admission Rank (ATAR) or equivalent, which is a score between 0.00 and 99.95 based on high school matriculation examinations, indicating a student's position in their cohort [3].…”
Section: Introductionmentioning
confidence: 99%
“…The UMAT was devised by the Australian Council for Educational Research, and consists of three sections: logical reasoning and problem solving; understanding people; and non-verbal reasoning. Most undergraduate medical programs in Australia use ATAR and UMAT outcomes to select a smaller group of applicants for additional selection processes, which may include interviews, psychological tests, or both [2,[6][7][8][9]. Most of the literature focusing on the efficacy of selection to medical programs focuses on the final stage of the selection process; that is selection from the pool of applicants who were successful in being offered an interview [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a societal viewpoint, the admission procedure resulting in the lowest proportion of rejected potentially successful students would contribute best to the development and use of human potential. To date, we have not encountered other methods that provide information on the proportions of both types of mistakes resulting from different tools and criteria, though methods complementary to regressions have been reported (e.g., Shulruf et al, 2018). In medicine, Signal Detection Theory is commonly used in investigating the accuracy of diagnostic tests.…”
Section: What Signal Detection Offersmentioning
confidence: 99%
“…In this issue of the MJA , Shulruf and his co‐authors 5 argue that completion of medical school is a better proxy measure of competence than exam performance per se because it better reflects real world outcomes and therefore, presumably, future patient safety. The authors analysed this outcome at five Australian and New Zealand universities, and found that prior educational attainment was the best predictor, aptitude testing (the Undergraduate Medicine and Health Sciences Admission Test [UMAT]) and interview not markedly improving discrimination between students who succeeded or failed.…”
mentioning
confidence: 99%